Effect of spray forming on evolution of microstructure and mechanical behavior of Mg-9Al-1Zn alloy - 余红燕 黄进峰 李永兵 崔华 何建平 张济山 (Transactions of Nonferrous Metals Society of China, 2007)
The cylindrical billet of Mg-9Al-1Zn alloy was produced by spray forming and hot extruded at 698-723 K with an extrusion ratio of 22：1, The microstructural evolution was investigated systematically. The mechanisms of grain refinement, solubility extension of Al and Zn elements in Mg matrix, and the precipitation of the second phase β-Mg17Al12 as well as their effect on the mechanical properties of the Mg-9Al-1Zn alloy were analyzed and discussed. The results show that the spray formed Mg-9Al-1Zn alloy has homogeneous equiaxed fine grains with the average grain size of 17 μm, of which the average grain size is refined further to 5 μm due to dynamic recrystallization during hot extrusion process. The evolution of size, proportion and distribution offl-Mg17Al12 phase was also observed and analyzed. The mechanical properties for the extruded rods are improved remarkably at ambient temperature.